THE ROLE OF VOCABULARY IN LEARNING FOREIGN LANGUAGES - Shagiyeva Gullola Erkinovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract. Vocabulary is not a decorative accessory in foreign language learning; it is the working engine that allows grammar, pronunciation, and communicative strategies to actually function. This article examines why lexical knowledge predicts success across the four skills, how vocabulary breadth (how many words a learner knows) and depth (how well those words are known) interact, and which teaching practices most reliably convert exposure into usable language.